Talking Local: Florida Consumers' Fresh from Florida Perceptions - Joy N. Rumble; Caroline G. Roper (EDIS)
As the final publication of the Talking Local series, this EDIS publication focuses on Florida consumer perceptions of Fresh from Florida. Fresh from Florida is a program administered by the Florida Department of Agriculture and Consumer Services (FDACS), which aims to advertise and promote Florida products (FDACS, 2013). This series focuses on ways Extension agents can assist Florida farmers and ranchers in the labeling, sale, and promotion of locally produced products. It provides Extension faculty who are interested in local food programming or who work with local food clientele with information about Florida consumers’ perceptions of local food. This 4-page fact sheet is a minor revision written by Joy N. Rumble and Caroline G. Roper, and published by the Department of Agricultural Education and Communication, November 2017.